Risk Factors for Impaired Patient-Reported Satisfaction and Increased Length of Hospital Stay Following Hysterectomy on Benign Indications in Premenopausal Women: a Study From the Swedish National Register for Gynecological Surgery - Borendal Wodlin, Ninnie (Geburtshilfe und Frauenheilkunde, 2020)
Introduction The aims of the study were to evaluate the impact of intra- and postoperative complications on satisfaction one year after hysterectomy for benign conditions, to determine risk factors for low patient satisfaction and to analyze whether complications were associated with the length of hospital stay.Material and Methods A retrospective study of 27 938 women from the Swedish National Register for Gynecological Surgery undergoing hysterectomy for benign conditions between January 2004 and June 2016. Data were obtained from prospectively collected pre-, peri- and postoperative forms. Statistical analyses were performed using multivariable logistic regression models. Crude and adjusted odds ratios and 95% confidence intervals are presented.Results More than 90% were satisfied with the hysterectomy. Dissatisfaction was associated with complications. Pelvic pain as indication, preoperatively having less expectations to get rid of symptoms or being alleviated from surgery, and current smoking were also risk factors for low patient satisfaction. Vaginal and abdominal subtotal hysterectomies were associated with high satisfaction. Occurrence of complications intra- and postoperatively before discharge was associated with increased length of hospital stay, as well as occurrence and severity of complications reported after discharge from hospital.Conclusions Complications were strongly associated with lower patient satisfaction. Preoperative expectations of surgery, indication, mode of surgery and life-style factors had impact on the satisfaction. Patient-centered information to ensure realistic expectations and prevention of complications seem to be essential to gain optimal patient satisfaction with surgery.
Keywords: hysterectomy; complications; satisfaction; length of hospital stay